2021
DOI: 10.3389/fclim.2021.716129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Ability of CMIP6 GCMS to Simulate the Boreal Summer Intraseasonal Oscillation Over Southeast Asia

Abstract: The boreal summer intraseasonal oscillation (BSISO) plays an important role in the intraseasonal variability of a wide range of weather and climate phenomena across the region modulated by the Asian summer monsoon system. This study evaluates the strengths and weaknesses of 19 Coupled Model Intercomparison Project Phase 6 (CMIP6) models to reproduce the basic characteristics of BSISO. The models' rainfall and largescale climates are evaluated against GPCP and ERA5 reanalysis datasets. All models exhibit intras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The dataset has been developed by the Research Institute for Humanity and Nature (RIHM) and the Meteorological Research Institute of Japan Meteorological Agency (MRI/JMA) and is available for all land areas in Asia from 1951 to 2015 at a spatial resolution of 0.25 • . The credibility of these datasets to represent rainfall characteristics over Asia has been documented in previous studies (e.g., He et al, 2019;Kim I. et al, 2019;Kim K. et al, 2019;Abatan et al, 2021;Khadka et al, 2022).…”
Section: Reanalysis and Simulationsmentioning
confidence: 68%
See 1 more Smart Citation
“…The dataset has been developed by the Research Institute for Humanity and Nature (RIHM) and the Meteorological Research Institute of Japan Meteorological Agency (MRI/JMA) and is available for all land areas in Asia from 1951 to 2015 at a spatial resolution of 0.25 • . The credibility of these datasets to represent rainfall characteristics over Asia has been documented in previous studies (e.g., He et al, 2019;Kim I. et al, 2019;Kim K. et al, 2019;Abatan et al, 2021;Khadka et al, 2022).…”
Section: Reanalysis and Simulationsmentioning
confidence: 68%
“…ENSO is an atmospheric-oceanic mode of variability on interannual time scales that is known to play a dominant role in controlling the climate variability of tropical and subtropical areas, with significant weather impacts (Todd et al, 2018;Roy et al, 2019;Pillai et al, 2021). The BSISO, which is characterized by 10-20-day and 30-60-day time scales, is known to play an important role in determining the intraseasonal variability of the Asian summer monsoon system (Li et al, 2015;Hsu et al, 2016;Lee et al, 2017;Yang et al, 2020;Abatan et al, 2021).…”
mentioning
confidence: 99%
“…Several generations of Coupled Model Intercomparison Project (CMIP) models, including the latest CMIP6, are unable to reproduce this variability [60][61][62]. A recent study has reported an unduly weak relationship between MSE and precipitation in these models [63]. It is also likely that these models do not capture the mechanisms influencing the build-up of MSE in the BL away from the equator, including over Indian landmass, and hence fail to promote off-equatorial precipitating convection.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Studies also have been performed to understand the changes in monsoon rainfall under CMIP6 simulations in the past (Gusain et al, 2020) and future (Ha et al, 2020; Wang et al, 2020). Abatan et al (2021) used CMIP6 models to look at the characteristics of boreal summer intraseasonal oscillation (BSISO) in SEA, while Zhu et al (2020) assessed the performance of CMIP6 models in simulating climate extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also have been performed to understand the changes in monsoon rainfall under CMIP6 simulations in the past (Gusain et al, 2020) and future (Ha et al, 2020;Wang et al, 2020). Abatan et al (2021) used CMIP6 models to look at the characteristics of boreal summer intraseasonal oscillation (BSISO) in SEA, while Zhu et al (2020) assessed the performance of CMIP6 models in simulating climate extremes. Cai et al (2015) suggested that many climate models tend to reproduce stronger warming along the equator under warmer climate, which is related with the weaker evaporative warming damping in the equatorial region compared to the evaporative warming damping over the off-equator region.…”
mentioning
confidence: 99%